Adoption of blockchain technology in healthcare systems: benefits, potential applications, and challenges - Zalak, Tasnim Marwan (2024)
A Master of Science thesis in Biomedical Engineering by Tasnim Marwan Zalak entitled, “Adoption of blockchain technology in healthcare systems: benefits, potential applications, and challenges”, submitted in May 2024. Thesis advisor is Dr. Abdulrahim Shamayleh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).